Action planning modulates the representation of object features in human fronto‐parietal and occipital cortex. (25th July 2022) - Velji‐Ibrahim, Jena; Crawford, J. Douglas; Cattaneo, Luigi; Monaco, Simona
Abstract: The visual cortex has been extensively studied to investigate its role in object recognition but to a lesser degree to determine how action planning influences the representation of objects' features. We used functional MRI and pattern classification methods to determine if during action planning, object features (orientation and location) could be decoded in an action‐dependent way. Sixteen human participants used their right dominant hand to perform movements (Align or Open reach) towards one of two 3D‐real oriented objects that were simultaneously presented and placed on either side of a fixation cross. While both movements required aiming towards target location, Align but not Open reach movements required participants to precisely adjust hand orientation. Therefore, we hypothesized that if the representation of object features is modulated by the upcoming action, pre‐movement activity pattern would allow more accurate dissociation between object features in Align than Open reach tasks. We found such dissociation in the anterior and posterior parietal cortex, as well as in the dorsal premotor cortex, suggesting that visuomotor processing is modulated by the upcoming task. The early visual cortex showed significant decoding accuracy for the dissociation between object features in the Align but not Open reach task. However, there was no significant difference between the decoding accuracy in the two tasks. These results demonstrate that movement‐specific preparatory signals modulate object representation in the frontal and parietal cortex, and to a lesser extent in the early visual cortex, likely through feedback functional connections. Abstract : The visual cortex has been extensively studied to examine its role in object recognition but to a lesser extent to determine how action planning influences the representation of objects' features. We provide evidence that the same object properties can be differentially decoded in the fronto‐parietal and early visual cortex depending on the upcoming interactions with the object. These results suggest that movement‐specific preparatory signals modulate object representation in the visual cortex, likely through feedback functional connections.